Exhaled 8-isoprostane as a new non-invasive biomarker of oxidative stress in cystic fibrosis - Montuschi, P. (BMJ Group, 2000)
BACKGROUND—Cystic fibrosis is characterised by oxidative stress in the airways. Isoprostanes are prostaglandin isomers formed by free radical catalysed peroxidation of arachidonic acid. 8-Isoprostane is increased in interstitial lung diseases, asthma, chronic obstructive pulmonary disease, and adult respiratory distress syndrome. Exhaled nitric oxide (NO) and carbon monoxide (CO) are biomarkers of inflammation and oxidative stress in the airways, respectively. METHODS—Concentrations of 8-isoprostane in the breath condensate of 10 normal subjects and 19 patients with stable cystic fibrosis were measured using an enzyme immunoassay (EIA). Breath condensate is a non-invasive method of collecting airway secretions. Exhaled nitric oxide (NO) and carbon monoxide (CO) levels were measured by a chemiluminescence analyser. RESULTS—Concentrations of 8-isoprostane in the breath condensate of patients with stable cystic fibrosis were increased about threefold compared with normal subjects (42.7 (4.5) pg/ml vs 15.2 (1.7) pg/ml; p<0.005, 95% CI 14.6 to 40.9). 8-Isoprostane concentrations were negatively correlated with forced expiratory volume in one second in patients with cystic fibrosis (r = −0.61; p<0.005). Exhaled CO was also increased in patients with cystic fibrosis compared with normal subjects (6.7 (1.2) ppm vs 2.9 (0.3) ppm; p<0.05, 95% CI 0.2 to 7.4). 8-Isoprostane concentrations were significantly correlated with CO levels (r = 0.66; p<0.002). CONCLUSIONS—The results of this study show that oxidative stress is increased in cystic fibrosis and may be quantified by measuring 8-isoprostane concentrations in breath condensate.